Konstektualisasi Penafsiran Ayat Penerima Warisan Berdasarkan Pada Kemaslahatan Umat - Hadi Mungawan, Samsul (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The Qur'an is the holy book for Muslims and is a guide to life for every Muslim. To study the Qur'an, you need media that can translate the meaning of the verses contained in the Qur'an, one of which is tafsir. Interpretation is very useful for understanding and studying the Qur'an as a guide for every aspect of life on this earth. As devout Muslims, if someone has died and has assets, then these assets must be passed on to those entitled to them. Islam has provided instructions regarding inheritance of inheritance, of which the Qur'an is the main source of inheritance law. In this work, we will discuss the meaning of inheritance, history of inheritance, inheritance verses in the Koran, elements of inheritance and distribution of inheritance based on Islamic guidelines. Based on the benefit of the ummah, the reality and situation of the inheritance journey, especially for women, in detail it can be said as follows: pre-Islam did not get it at all while men got a full inheritance, then Islam came with the guidance of the Qur'an in its verse stating that women can heirs are one third while men are two thirds. Furthermore, in the current situation which is based on the reality where economic responsibilities can be played by women, inheritance also follows the existing law in dividing women's inheritance equally with men's share, existing inherited assets are divided equally by both men and women.  Keywords: Inheritance, verses of the Qur'an, recipients of inheritance